On the Synthesis Mechanism of TiN, ZrN, and HfN During Combustion of Mixtures of Aluminum Nanopowder with TiO2, ZrO2, and HfO2; Refractories and Industrial Ceramics; Vol. 60, iss. 4 - Root L. O. Lyudmila Olegovna (2019, 2019)
Title screen